Application of Linear Regression Method in Predicting Veil Sales (Case Study: Fauzan Kerudung Shop) - Fitri Amalini; Harefa, Ade May Luky (Journal of Data Science, Technology, and Artificial Intelligence, 2024)
The sales prediction system can support business transactions, especially those engaged in the trading sector, as an operational process that forecasts products to be sold in the future. One of the stores involved in the trading business is Toko Kerudung Fauzan. This kerchief store relies solely on estimates to determine the quantity of goods to be purchased from suppliers. This reliance on estimates has led to difficulties for the store owner in predicting future sales without performing calculations to maintain inventory levels in the store. Therefore, there is a significant need for a prediction system to determine kerchief sales in the future. The method employed for sales prediction is the Linear Regression Method. The number of data samples used consists of sales data collected from January to December 2022. Consequently, it can be stated that the decision to predict sales in 2023 shows a decline.